PERANCANGAN ULANG SEKOLAH MENENGAH KEJURUAN NEGERI 1 SUNGAI RUMBAI KABUPATEN DHARMASRAYA - 195-210 , Dedet (Universitas Negeri Padang, 2013)
The purpose of this study is to realize a conceptual foundation for designing an educational facility representative and accommodating at SMK 1 Sungai Rumbai Dharmasraya. This study discusses the planning and architectural design, principles of arrangement of buildings, land management and land requirements. Observations for re-planning is done at the school directly. Primary data is presented in the form of special reviews on existing conditions of existing school buildings, and secondary data in the form of an overview of the geographical and economic conditions of communities around the site. Analysis conducted for this plan includes the analysis of users at SMK N 1 Sei.Rumbai, analysis of the activities in the school, room types and groupings analysis, dimensional analysis required space, parking space needs analysis, analysis of land utilization and review of the and use requirements. This study produced a design concept that includes zoning, spatial orientation, the relationship of space, form and space as well as the achievement of circulation. This concept produces an image that is more supportive services school planningbased on education Minimum Service Standards.Key words : redesign, lang management, drawing